Асинхронные автоматы, сравнивающие треки - Шахбазян, К.В.; Шукурян, Ю.Г. (Кибернетика и системный анализ, 2012)
Наведено алгоритми розв’язання декiлькох задач порiвняння трекiв Мазуркевича. Алгоритми зводяться до побудови автоматiв, що розпiзнають вiдповiднi рацiональнi трековi мови. Розглянуто трековi мови, пов’язанi з розв’язанням конретних задач, що мають аналоги в науцi про рядки. The paper presents algorithms for solving several matching problems of Mazurkiewicz traces. These algorithms are reduced to the construction of automata that recognize the corresponding rational trace languages. Rational trace languages and their properties were studies by many authors. The paper considers trace languages related to specific problems that have analogs in stringology